An audit of standards of the 'see and treat' approach in women with a high-grade squamous intraepithelial lesion on Pap smears - C. Kietpeerakool (2018)
This study was undertaken to audit the performances of the 'see and treat' approach in women with a high-grade squamous intraepithelial lesion (HSIL) cytology at Chiang Mai University Hospital using selective criteria from the National Health Service Cervical Screening Programme (NHSCSP) 2004 guidelines. Women with a HSIL smear, who had undergone colposcopy and immediate loop electrosurgical excision procedure (LEEP) during June 2006 and September 2008, were reviewed. The standard measurement was determined by the following criteria: (1) the proportion of women treated at the first visit who have evidence of cervical intraepithelial neoplasia (CIN) on histology to be >90%; (2) the primary haemorrhage must be <5%; (3) the proportion of patients admitted as inpatients owing to treatment complication to be <2%. Of 247 women in this study, the histopathological results were as follows: CIN II-III, 188 (76.1%); cancer, 31 (12.6%); adenocarcinoma in situ, 5 (2.0%); CIN I, 5 (2.0%); and no CIN, 18 (7.3%). The prevalence of CIN I or higher was 92.7%. Primary haemorrhage was observed in 13 (5.3%) women. Four (1.6%) women were admitted as inpatients because of LEEP-related complications. In conclusion, the 'see and treat' approach in our institute has acceptable overtreatment and complication rates. © 2009 Informa Healthcare USA, Inc.